Bilingualism of Hoho Characters in the Animated Series Ibra Berkisah: An Interactional Sociolinguistic Review - Yanah, Rohmah Barokah Toriqul; Yarno, Yarno; Hermoyo, Panji (Universitas Muhammadiyah Malang, 2025)
This research is motivated by the growing phenomenon of bilingualism in children's animated media, but has not been widely studied from an interactional sociolinguistic perspective. The animated series Ibra Berkisah, produced by Manara, was chosen as the object of research because it features the character Hoho, who uses two languages, namely Indonesian and English, in the context of Islamic boarding schools. The purpose of this study is to analyze the forms of bilingualism that appear in the Hoho character, including the phenomena of code-switching and code-mixing used in interactions between characters, and to explain their function in the formation of identity and character. This study uses a qualitative descriptive method with observation, documentation, and transcription of dialogue from eight representative episodes of the Ibra Berkisah series obtained from the official YouTube channel. Data were analyzed using the interactive model of Miles, Huberman, and Saldana through the processes of reduction, presentation, and conclusion. The results show that bilingualism in Hoho functions as a communication tool, a symbol of social status, a means of emotional expression, and a mechanism for adaptation to the Islamic boarding school environment. The shift from English to Indonesian dominance and the use of religious terms signify the internalization of spiritual values, leading to character transformation. Thus, the bilingualism in Ibra Berkisah not only reflects linguistic variation but also serves as a medium for social, moral, and identity learning for young audiences.